Use the Pythagorean theorem: a^2 + b^2 = c^2 a = sqrt (c^2 - b^2) Where: a=the height (pyramid height from base to peak) b=the base length c = the hypotenuse (slant) length
You need some information about the height of the pyramid and the formula will depend on whether you have the vertical height or the slant height or the length of a lateral edge.
If you make a line from the top of the pyramid to the center of the base, you have the height of the pyramid. This meets at the midsegment of a line going across the base. Since the height of a pyramid is perpendicular with the base, get this: the height, a line of 1/2 the length of the base, and the slant height form a right triangle. So, you can use the Pythagorean Theorem! For example, if the base length is 6 and the height of the pyramid is 4, then you can plug them into the Pythagorean Theorem (a squared + b squared = c squared, a and b being the legs of a right triangle and c being the hypotenuse). 1/2 the length of the base would be 6 divided by 2=3. 3 squared + 4 squared = slant height squared. 9+16=slant height squared. 25= slant height squared. Slant height=5 units. You're welcome!
210 in 2
I don't know not mine
Why do you need to FIND the slant height if you have the [lateral height and] slant height?
SA = 3as + 3sl a = apothem length (length from center of base to center of one of the edges). s = length of a side l = slant height
Slant height is 39.98 cm
if you know the height and the apothem, use pythagorean theorem to solve for it.
Knowing the slant height helps because it represents the height of the triangle that makes up each lateral face. So, the slant height helps you to find the surface area of each lateral face.
The height would be The square root of the square of the slant surface length minus the square of the radius of the cone at the base.